A comprehensive design, optimization and development methodology of a wasted heat recovery boiler using serrated fins and extensive surface in a bulky CCPP. (February 2021) - Mohtaram, Soheil; Sun, Yonghui; Sun, Hongguang; Abrishami, Arya; Omidi, Mohammad; Lin, Ji
Abstract: This paper describes the requirements and the difficulty encountered in preparing the data for the consumption calculations of a waste heat recovery boiler (WHRB). The study is performed based on continuous monitoring of the operating data by considering the extensive thermal surfaces and a large number of small-serrated fins. The recovery boiler efficiency improved using optimization of temperature profile by better surface arrangement. Then, the suggested designed waste heat recovery boiler is accessible and conducted in a real combined cycle power plant (CCPP). The CCPP optimization is performed based on the new WHRB with and without optimal saturation temperature, and the recovery boiler optimal temperature is obtained based on the objective function. The founded values of the CCPP at different temperatures are verified and compared to the regular operation. The important findings include four categories. First, the gas temperature of the recovery boiler will decrease slightly while the efficiency will increase by increasing the load changes. Second, the dependency of the decision parameters of the CCPP to the ambient temperature is effectively high, and any changes in the efficiency depending on the ambient temperature. Third, the exergy efficiency increment without affecting the total exergy can be performed by using the low-pressure saturation temperature as a decision-making parameter. Forth, 17.9% improvement in the entire cycle efficiency and a 2.14% increase in WHRB exergy are observed after incrementing the cost by 14.48%.